2019
DOI: 10.1556/2006.8.2019.60
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias in Internet users with problematic use of social networking sites

Abstract: Background and aims: Evidence from the field of addictive disorders suggests that attentional bias for stimuli related to a substance or activity of abuse (e.g., gambling) exacerbates the addictive behavior. However, evidence regarding attentional bias in PIU is sparse. This study aims to investigate whether individuals who express problematic tendencies toward social networking sites (SNS), a subtype of PIU, show attentional bias for stimuli associated with social media. Methods: Sixty-five participants perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 39 publications
1
24
1
Order By: Relevance
“…Again, this is in contrast to previous work on nonsubstance related addictions as shown by Ciccarelli et al (2016;Gambling), Jeromin et al (2016;Gamers), and Pekal et al (2018;Internet Pornography Use), which reported positive associations between levels of attention bias and use/ severity measures. Moreover, while Nikolaidou et al (2019) did report an association between the level of urge to be online and attentional dwell time to social media related stimuli, this effect was based on a small sample size (N 5 16).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Again, this is in contrast to previous work on nonsubstance related addictions as shown by Ciccarelli et al (2016;Gambling), Jeromin et al (2016;Gamers), and Pekal et al (2018;Internet Pornography Use), which reported positive associations between levels of attention bias and use/ severity measures. Moreover, while Nikolaidou et al (2019) did report an association between the level of urge to be online and attentional dwell time to social media related stimuli, this effect was based on a small sample size (N 5 16).…”
Section: Discussionmentioning
confidence: 91%
“…To our knowledge, only one paper has been published to date which has investigated the presence of an attentional bias in social media users. Nikolaidou, Fraser, and Hinvest (2019) reported an attentional bias, in the form of increased attentional dwell times, to social media related stimuli in a group of social media users. However, this finding could be limited by the task, which used over-sized social media images (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Since little is known about the cognitive variables related to social network addiction, the present study investigates the role of attentional style as moderator variables between time perspectives and social network addiction. As stated by prior literature, attentional style is related both with time perspectives [23] and with addictive behaviors such as social network addiction [25]; therefore, we retain that attentional style might be responsible for individual variations in the relationship between time perspectives (all dimensions) and social network addiction. More specifically, internal vs. external attentional style might be responsible for the ways in which people select and focus their attention on their internal thoughts about past, present, or future life events and external interactive stimuli provided by social networking sites.…”
Section: Introductionmentioning
confidence: 83%
“…A recent study by Nikolaidou, Fraser, and Hinvest [25] reported that attention could affect social network addiction, too. Indeed, authors showed that high social network addiction individuals focus more on processing visual stimuli related to social networking sites (e.g., Facebook, Instagram, and WhatsApp logos) than control images (e.g., everyday objects such as a cup, clock, and umbrella).…”
Section: Attention and Social Network Addictionmentioning
confidence: 99%
“…Many studies are limited by their atheoretical approach and do not offer an explanation of the conditions under which compulsive SNS use develops or how it is maintained [ 3 ]. Nevertheless, a growing body of research has begun to employ behavioural experimental paradigms to examine the cognitive and motivational processes (such as inhibitory control and attentional bias) that might contribute to general SNS use behaviours and the development and maintenance of problematic SNS use [e.g., 4 6 ]. If problematic SNS use is to be considered a candidate behavioural addiction then such studies investigating the cognitive/motivational components of SNS use are important in order to demonstrate that it warrants recognition as an addictive disorder [ 7 ].…”
Section: Introductionmentioning
confidence: 99%